2020
DOI: 10.4103/abr.abr_213_18
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular strain: A reliable predictor of short-term outcomes in patients with anterior wall myocardial infarction without heart failure

Abstract: Background: Left ventricular ejection fraction (LVEF) is a key determinant in decision-making after acute myocardial infarction (MI). Little is known of its relationship with left ventricular Strain and N-Terminal fragment of pro-B-type Natriuretic Peptide (NT-pro-BNP) following acute anterior wall MI (AWMI). Materials and Methods: We conducted a prospective cohort study of patients with a diagnosis of acute AWMI and the absence of overt heart failure (HF). Assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The current study found that LV strain was not able to predict major adverse cardiovascular events (MACE) at one-month follow-up, but when comparing 2 groups in the presence and absence of events, for the clinical and echocardiographic variables exhibits substantial differences. LV Strain was found to be signi cantly lower in patients with MACE than event free group .Hence GLS was proved to have higher sensitivity in detecting subclinical LV dysfunction when compared to LVEF4.In contrary, studies proved that apart from NT-pro BNP and LVEF, PSLV's and PSLS are good predictors of adverse outcomes at 30 day follow up 9 .…”
Section: Relationship Between LV Gls and Major Adverse Cardiac Eventsmentioning
confidence: 95%
“…The current study found that LV strain was not able to predict major adverse cardiovascular events (MACE) at one-month follow-up, but when comparing 2 groups in the presence and absence of events, for the clinical and echocardiographic variables exhibits substantial differences. LV Strain was found to be signi cantly lower in patients with MACE than event free group .Hence GLS was proved to have higher sensitivity in detecting subclinical LV dysfunction when compared to LVEF4.In contrary, studies proved that apart from NT-pro BNP and LVEF, PSLV's and PSLS are good predictors of adverse outcomes at 30 day follow up 9 .…”
Section: Relationship Between LV Gls and Major Adverse Cardiac Eventsmentioning
confidence: 95%
“…Myocardial strain can be used to assess both global systolic function and systolic and diastolic function. Strain has substantial potential to be of diagnostic and prognostic value, and most of the clinical evidence for strain measurement is obtained by echocardiography [11]. However, inadequate image quality and considerable observer variability are well-known limitations of echocardiographic techniques and affect myocardial strain measurement reliability [4].…”
Section: Plos Onementioning
confidence: 99%